Alzheimer\'s Disease: Yesterday, Today, Tomorrow - Farid Fadaei; Zahra Niknam (University of Social Welfare & Rehabilitation Sciences, 2007)
Alzheimer's disease is the most common and well - known cause of dementia, as a progressive, irreversible brain disorder that affects cognitive function, personality, thought, perception and behaviour. Alzheimer's disease is the fourth leading cause of death in western countries. Interesting to know that this disease was unknown in medical community till 100 years ago and had no name. Dr. Alois Alzheimer, a German psychiatrist was the person who suspected the presence of this new illness and by succinct clinical, neuroanatomic, and neuropathologic examination of some cases; including the first known case of this disease- a woman named Auguste Deter- documented it. In further Emil Kraepe1inby knowing about the cases that Dr. Alzheimer reported, and another reports of this disease that were published in the first decade of the twentieth century, set the name of Alzbeimer on this new disease. Descriptions of Dr. Alzheimer and Kraepelin are the same as the present day descriptions of this disease. Electron microscopy, quantitative morphology and modem biochemistry emerging in the second half of the twentieth century opened a new era in dementia research with description of the ultra structure and biochemistry of senileplaques and neuronfibrillary tangles, the major disease markers of Alzheimer's disease. Basic research gave insight into the molecular genetics and pathophysiology of Alzheimers disease and based on the biochemical findings, new pharmacological treatment options were opened. The future attempts will probably be concentrated on the prevention of this disease. Oxidative stress, excessive transition metal ions, and misfolded / aggregated proteins and inflammation are among the probable causes of Alzheimer's disease and the future research will focus on their better understanding and prevention of their occurrence. As the last word, stem cells grafts that in animals have led to remarkable improvement of brain function may also be a promising course in the cure of Alzbeimer's disease in the future.